„Dopalacze” – nieprzewidywalne narkotyki. Problem społeczno-prawny - Matyjek, Sebastian (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
The aim of this article is to present the problem of new psychoactive substances – designer drugs. New drugs are undoubtedly a social and legal problem. The existing legal regulations lag behind the producers of designer drugs who use all the available methods to bypass the law, which is a kind of race between criminals and the legislator. In the author’s opinion the current methods used by the Polish legislator are not effective. Prohibition policy has led to the emergence of new deadly agents such as designer drugs. When looking for an answer to the question of how to fight new drugs, we need to look at various instruments, not just the criminal law. According to the author the adoption of a liberal strategy involving the legalization of soft drugs is an effective solution. Legal soft drugs would put an end to the prevalence of high-risk designer drugs.